Effectiveness of risk-based caries management among Chinese preschool children: a randomized controlled single-blind trial - Hao-feng Jiang; An-tian Shi; Jing Li; Yu-han Zhang; Jing Yang (BMC, 2024)
Abstract Background Early childhood caries (ECC) remain a serious oral health problem on a global scale. Risk-based caries management (RBCM) implemented in some parts of the world has been effective in preventing ECC. However, there is a lack of prospective research on the application of RBCM among Chinese children, and little is known about its effectiveness. The purpose of this study was to evaluate the effectiveness of RBCM in preventing caries among children aged 3-5 years in Wanzhou District, Chongqing Municipality, China. Methods Three- to five-year-old children from four kindergartens in Wanzhou were randomly selected for baseline dental examination and caries risk assessment (CRA) and randomly assigned to the experimental group (EG) or the control group (CG) according to the kindergarten. The EG received caries prevention measures of different intensities based on the child's caries risk level. The CG received full-mouth fluoride twice a year according to standard prevention, regardless of their caries risk. One year later, another dental examination and CRA were conducted, to observe changes in the decayed, missing, and filled teeth (dmft) index and caries risk, and to analyze potential factors that may affect the incidence of new caries. Results Complete data were collected from 291 children (EG, N = 140, 84.8%; CG, N = 181, 83.4%). A total of 25.7% of the EG and 50.3% of the CG children developed new caries, with newly added dmft scores of 0.54 ± 1.12 and 1.32 ± 1.72, respectively (P < 0.05). Multivariate logistic regression indicated that children living in rural areas, assigned to the CG, and rated as high-risk at baseline were more likely to develop new caries (P < 0.05). The proportion of children with an increased caries risk in the EG was significantly lower than that in the CG (P < 0.05). Conclusions RBCM effectively prevented new caries in 3- to 5-year-old Wanzhou children and reduced the proportion of children at increased risk of caries. It is an effective approach for preventing ECC. Clinical trial registration This trial was registered in the Chinese Clinical Trials Register. The registration number was ChiCTR230067551 (11/01/2023).